Dune - Herbert, Frank (New York : Ace Books, 1999)
Future space fantasy concerning a time when the human race has reached a point of intellectual stagnation and receives the help of a space-age Messiah and prophet.
Keywords: Dune (Imaginary place) -- Fiction; Science fiction